Stylizacja na język potoczny w tłumaczeniu kanadyjskiej dramaturgii mniejszościowej na przykładzie polskiej wersji sztuki La Défaite Georges’a Bugneta - Małgorzata Czubińska (Ksiegarnia Akademicka Publishing, 2021)
Colloquial stylization in French‑Canadian minority theatre: The case of Georges Bugnet’s La Défaite and its translation into Polish